Ethics in social communications - Valim, Ricardo (Seven Editora, 2023)
With the rapid development of the media, the need for ethical reflection on the media is clear. Because they bring with them great possibilities of interaction between human beings, regardless of their geographical location. Great novelties in resources appear all the time bringing in its structure remnants of technologies that once initiated the progress of communications. However, these same advances can both lead to projects that actually promote the human being and can also contribute to its decline. Therefore, the objective of this research is to seek to understand how the media are important for various fields of human activity from economics to religion and also to understand how these media can negatively influence society. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-042